Nanoparticle‐Mediated Blocking of Excessive Inflammation for Prevention of Heart Failure Following Myocardial Infarction. Issue 32 (3rd July 2021) - Kwon, Sung Pil; Hwang, Byung‐Hee; Park, Eun‐Hye; Kim, Han Young; Lee, Ju‐Ro; Kang, Mikyung; Song, Seuk Young; Jung, Mungyo; Sohn, Hee Su; Kim, Eunmin; Kim, Chan Woo; Lee, Kwan Yong; et al.
Abstract: Severe cardiac damage following myocardial infarction (MI) causes excessive inflammation, which sustains tissue damage and often induces adverse cardiac remodeling toward cardiac function impairment and heart failure. Timely resolution of post‐MI inflammation may prevent cardiac remodeling and development of heart failure. Cell therapy approaches for MI are time‐consuming and costly, and have shown marginal efficacy in clinical trials. Here, nanoparticles targeting the immune system to attenuate excessive inflammation in infarcted myocardium are presented. Liposomal nanoparticles loaded with MI antigens and rapamycin (L‐Ag/R) enable effective induction of tolerogenic dendritic cells presenting the antigens and subsequent induction of antigen‐specific regulatory T cells (Tregs). Impressively, intradermal injection of L‐Ag/R into acute MI mice attenuates inflammation in the myocardium by inducing Tregs and an inflammatory‐to‐reparative macrophage polarization, inhibits adverse cardiac remodeling, and improves cardiac function. Nanoparticle‐mediated blocking of excessive inflammation in infarcted myocardium may be an effective intervention to prevent the development of post‐MI heart failure. Abstract : Liposomal nanoparticles loaded with both antigen and rapamycin (L‐Ag/Rs) are fabricated as novel therapeutics for myocardial infarction (MI). L‐Ag/Rs generate regulatory T cells and reparative M2 macrophages in infarcted heart, inducing immune tolerance with antigen‐specific manner. The reparative phase elicited by L‐Ag/R inhibits excessive inflammation and adverse cardiac remodeling in infarct region, improving cardiac function.